Fatal pediatric case of Kounis syndrome and sepsis: a case report - Tamara Berezna; Olha Synoverska; Nadiya Fomenko; Iryna Pylyuk; Khrystyna Lazurkevych; Viktoria Bedei; Taras Kotyk (International Journal of Emergency Medicine)
Abstract Background Kounis syndrome is a hypersensitivity reaction that induces acute coronary artery events, nevertheless its pediatric occurrence remains rare and often underdiagnosed. This report describes a fatal case of Kounis syndrome triggered by ceftriaxone-lidocaine administration in a child, in the context of sepsis and multiple organ dysfunction syndrome. Case presentation A 4-year girl with a history of cyclic vomiting syndrome, was admitted to the ICU with severe lethargy and pallor 30 min after the second intramuscular injection of ceftriaxone, which had been prescribed for vomiting, diarrhea, and fever. Her laboratories were pertinent for a metabolic acidosis, neutrophilic leukocytosis, renal dysfunction, elevated cardiac markers (troponin I and cardiac-type creatine phosphokinase), EKG signs of myocardial ischemia, bilateral bronchopneumonia, and right lower multifocal pneumonia. Despite intensive management, the patient’s condition continued to deteriorated, which lead to multiple organ dysfunction and eventual death. Conclusion This case highlights the need for heightened clinical awareness of Kounis syndrome in pediatric settings, especially in patients with underlying infections. This case underscores the fatal potential of undiagnosed Kounis syndrome in the pediatric population and highlights the urgent need for enhanced vigilance and multidisciplinary preparedness.